Pentingnya Menanamkan Nilai-Nilai Pancasila pada Siswa Kelas IV di Sekolah Dasar - Desclarista Salwa Putri; Vallen Syiah; Fadila Ramadhani; Ari Suriani; Afriza Media (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This article aims to investigate the importance of instilling Pancasila values ​​in grade IV elementary school students as the main basis for children's moral development. This study was conducted using a literature review method through analysis of various articles from sources such as academic journals and Google Scholar, using the keywords "Instilling Pancasila Values ​​in Elementary Schools" that are relevant to the topic discussed. Pancasila functions as the nation's philosophy of life, which builds national identity while providing guidelines for acting morally and ethically for all individuals. Therefore, Pancasila values ​​must be instilled from an early age so that children can develop personalities that are in line with these values. The results of this study show that instilling Pancasila values ​​has a significant impact on the formation of behavior, character, and ethics of students at the elementary school level.